Surgical Treatment of Pancreatic Ductal Adenocarcinoma - Satoi, Sohei (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book contains the art and science in current standards of surgical treatment of pancreatic ductal adenocarcinoma. It explains the clinical role of surgical resection during multimodal treatment in patients with pancreatic ductal adenocarcinoma, novel surgical techniques including extended pancreatectomy and minimally invasive surgery, risk of cancer in IPMN, and the clinical importance of liquid biopsy.